Microglia in a Dish—Which Techniques Are on the Menu for Functional Studies? - Aktories, Philipp; Petry, Philippe; Kierdorf, Katrin (Frontiers in Cellular Neuroscience, 2022)
Microglia build the first line of defense in the central nervous system (CNS) and play central roles during development and homeostasis. Indeed, they serve a plethora of diverse functions in the CNS of which many are not yet fully described and more are still to be discovered. Research of the last decades unraveled an implication of microglia in nearly every neurodegenerative and neuroinflammatory disease, making it even more challenging to elucidate molecular mechanisms behind microglial functions and to modulate aberrant microglial behavior. To understand microglial functions and the underlying signaling machinery, many attempts were made to employ functional in vitro studies of microglia. However, the range of available cell culture models is wide and they come with different advantages and disadvantages for functional assays. Here we aim to provide a condensed summary of common microglia in vitro systems and discuss their potentials and shortcomings for functional studies in vitro.